Exploratory Study to Determine Perceptions of Globalization and Global Career - Nayyar, Ruchi (Indian Journal of Computer Science, 2018)
Using social media for perceptions based study is a common practice. This study makes use of microblogging social network site Twitter to understand public opinions and trends around globalization. Two thousand tweets were analyzed to study public perceptions ofglobalization, global careers and internationalization. Additionally, exploratory analysis was performed by administering questionnaires to discover the positive and negative perceptions about globalization and global careers.Â Countries and companies can develop strategies around the outcomes to address the economic and social impacts of globalization. Methodology and findings Two thousand tweets were extracted from Twitter database using R tool. Subsequent mining of the unstructured data revealed convergent and divergent perceptions of globalization dynamics. In the second component of the research, respondent data of 210 people were collected using convenience sampling to meet the research objective. Four factors emerged which divided the perceptions around global career and globalization into positives and negatives. Research limitations/implications Twitter research involves sampling and filtering restrictions. The outcomes of this research are not representative of the entire Twitter community. Originality/value To the best of my knowledge, this is first studyto utilize Twitter to understand peopleâ€™s perceptions on globalization.Â